The home, nations and empires, and ephemeral exhibition spaces : 1750-1918 - Bauer, Dominique; Murgia, Camilla, 1977- (Spatial imageries in historical perspective., 2021)
"This book explores ephemeral exhibition spaces between 1750 and 1918. The chapters focus on two related spaces: the domestic interior and its imagery, and exhibitions and museums that display both national/imperial identity and the otherness that lurks beyond a country's borders. What is revealed is that the same tension operates in these private and public realms; namely, that between identification and self-projection, on the one hand, and alienation, otherness and objectification on the other. In uncovering this, the authors show that the self, the citizen/society and the other are realities that are constantly being asserted, defined and objectified. This takes place, they demonstrate, in a ceaseless dynamic of projection versus alienation, and intimacy versus distancing." -- Back cover.